Energy Monitoring Programme for Social Housing in Ireland: Pre- and Post- Retrofitting - SINNOTT, DEREK; DYER, MARK (My University, 2012)
There is a scarcity of empirical data to demonstrate the actual benefit of energy efficient retrofitting in the residential sector. The Irish official methodology for calculating the energy rating of dwellings only offers an indication of energy performance. This paper describes the methodology involved in the initial stages of an on-going longitudinal energy monitoring programme to determine actual energy savings brought about by a building retrofitting programme for social housing in Kilkenny, South East Ireland. The bespoke system was designed to monitor whole building energy use for one year pre- and post- retrofitting. The wireless system installed in nine dwellings regularly logs indoor temperature, humidity, volatile organic compounds, gas and segregated electricity. Raw data is relayed to a data concentrator within the building and via a network to a secure database. Basic cleaning of the data is carried out prior to presentation for analysis on a secure website. The monitoring system is designed to provide an understanding of energy consumption patterns and energy wastage in social housing. The paper explains and reviews the monitoring system employed and highlights some of the key lessons learnt during the planning and installation of equipment. Gas meters which do not have a pulse output and solid fuel use pose the largest challenge to monitor. The paper makes suggestions to researchers and industry professionals for future domestic energy monitoring systems.
PUBLISHED
Keywords: Existing Dwelling; Energy Monitoring; Energy Performance